Analysis of ICD-9-CM Coding Accuracy in the Reimbursement Claim Process for INA-CBGs Compliance - Ervita Nindy Oktoriani; Anna Rosarini; Idham Alhafidz Lubis (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
This study aims to analyze the accuracy of ICD-9-CM coding in Cathlab procedure claims submitted to BPJS Kesehatan under the INA-CBGs reimbursement system at RSI Aisyiyah Malang. Accurate coding is critical for determining appropriate claim grouping and tariff calculation within Indonesia’s national health insurance scheme. The research employed a mixed-methods approach, combining quantitative analysis of 244 Cathlab claims from 2024 with qualitative insights obtained through document review, interviews, and direct observation. The results showed that 182 claims (74.59%) were accepted as accurate and complete, while 62 claims (25.41%) were returned as pending. Common causes of claim inaccuracy included missing supporting documents (37.10%), incorrect ICD-9-CM codes (27.42%), and nonspecific diagnoses (19.35%). Procedural miscoding, such as omitting dual catheterization codes or stent-related procedure codes, was identified as a frequent issue, significantly impacting claim grouping and reimbursement. The study highlights systemic challenges related to documentation quality, coder competency, and institutional claim verification processes. These challenges result in delays, incorrect payments, and administrative inefficiencies, posing barriers to effective reimbursement. The findings underscore the importance of implementing Clinical Documentation Improvement (CDI) strategies, improving coder training, and transitioning to newer coding systems such as ICD-10 or ICD-11. Upgrading to these systems will support better coding accuracy, enhance claim processing efficiency, and ensure more appropriate reimbursement. Strengthening these components is essential to ensure the integrity of Indonesia’s health financing system, improve operational workflows, and ensure that healthcare providers receive timely and accurate reimbursement for services rendered. This study provides a comprehensive evaluation of the current state of coding practices in Indonesian healthcare institutions and offers actionable recommendations for improving coding accuracy and claims processing.